Race and Arab Americans Before and After 9/11: From Invisible Citizens to Visible Subjects by Amaney Jamal and Nadine Naber, eds. (Syracuse, New York: Syracuse University Press, 2007. 378 pages.) (American Journal of Islam and Society, 2009)
The present American moment has been hailed by some as inaugurating anera of “post-black” politics with the candidacy and election of PresidentBarack Obama. Obama’s election, in the words of Manning Marable, indicatesthe possibility that America has entered “an age of post-racial politics,in which leadership and major public policy debates would not be distortedby factors of race and ethnicity” (“Racializing Obama: The Enigmaof Post-Black Politics and Leadership,” Souls 11, no. 1 [2009]: 1-15). Whilehis campaign and victory heralded the message of hope in a “post-racial”landscape, the dangers of stumbling blindly onto the bandwagon could, andin some cases have, result(ed) in erasing race’s enduring presence in contemporaryAmericanpolitics.Thus, there is perhaps no better time for the publication of Race andArab Americans Before and After 9/11, as it counters contemporary publicamnesia by reminding us that race and inequality still permeate the lives ofminority populations. Speaking to an interdisciplinary audience and seekingto fill a critical gap in the field ofAmerican racial and ethnic studies, this collectionof essays highlights the complex and slippery ways in which race permeatesArab andArab-American engagements with the American socialhierarchy.Foregrounding the complexities of Arab-American racial formationas a critical site of inquiry in the introduction, Nadine Naber calls formoving beyond the usual liberal multiculturalist “add on” approach in orderto consider “the shifting and contradictory historical contexts throughwhichArabAmericans have engaged with immigration, assimilation, andracialization” (p. 4). In a concise but evocative historical précis, she showshow “anti-Arab racism represents a recurring process of the constructionof the Other within U.S. liberal politics in which long-term trends of racialexclusion become intensifiedwithinmoments of crisis in the body politic…”(p. 31) ...